Reassembly and protection of small nuclear ribonucleoprotein particles by heat shock proteins in yeast cells. - Bracken, A P (1999)
The process of mRNA splicing is sensitive to in vivo thermal inactivation, but can be protected by pretreatment of cells under conditions that induce heat-shock proteins (Hsps). This latter phenomenon is known as "splicing thermotolerance". In this article we demonstrate that the small nuclear ribonucleoprotein particles (snRNPs) are in vivo targets of thermal damage within the splicing apparatus in heat-shocked yeast cells. Following a heat shock, levels of the tri-snRNP (U4/U6.U5), free U6 snRNP, and a pre-U6 snRNP complex are dramatically reduced. In addition, we observe multiple alterations in U1, U2, U5, and U4/U6 snRNP profiles and the accumulation of precursor forms of U4- and U6-containing snRNPs. Reassembly of snRNPs following a heat shock is correlated with the recovery of mRNA splicing and requires both Hsp104 and the Ssa Hsp70 family of proteins. Furthermore, we correlate splicing thermotolerance with the protection of a subset of snRNPs by Ssa proteins but not Hsp104, and show that Hsp70 directly associates with U4- and U6-containing snRNPs in splicing thermotolerant cells. In addition, our results show that Hsp70 plays a role in snRNP assembly under normal physiological conditions.